Typomorphic characteristic features of accessory ilmenite in granitoids of the polyphase Aleisk-Zmeinogorsk complex (N-W Rudny Altai area); MATEC Web of Conferences; Vol. 85 : Chemistry and Chemical Technology in XXI Century (CCT 2016) - Novoselov K. L. Konstantin Leonidovich (2016, 2016)
Title screen